A Critical Analysis of the Liability of Directors in Light of the Unwarranted Shareholder Involvement in South African State-Owned Enterprises - Joubert, E.P. (University of Pretoria, 2020)
Mini Dissertation (LLM)--University of Pretoria, 2019.